Assessment of attitude, practice, and barriers to pharmaceutical care among community pharmacists in Ibadan (2022)
Background: Pharmaceutical care (PC) is a professional responsibility of a pharmacist that involves medication management with the overall goal of improving the quality of life of patient. OBJECTIVES: To evaluate the attitude, practice, and barriers to PC among community pharmacists in Ibadan. METHOD: A cross-sectional survey was conducted among community pharmacists between May and July 2021, with the aid of a self-administered questionnaires, information on socio-demographic characteristics, practice, attitudes, and barriers to PC was obtained. A consecutive sampling technique was used for participants’ enrolment. Participating pharmacists must have had a minimum of one-year practice experience in a community pharmacy. Pharmacy students, interns, non-pharmacist attendants, and community pharmacists who were absent from their pharmacies during the study were excluded. Data were summarized with descriptive statistics. RESULTS: Over 12 weeks, 120 survey were collected (90.9% response rate). About (115; 95.8%) of respondents had good practice of PC and reported that pharmaceutical care is a timely innovation to pharmacy practice. However, only (62; 52.0%) had positive attitude and (117; 97.5%) believed more pharmaceutical care could be provided. Regarding their practice, most respondents (118; 98.3%) stated pharmaceutical care involves monitoring improvement in patient response to treatment and adherence to treatment regime and counselling patients with drug therapy problems. The top detected barriers for PC provision included insufficient time (71; 59.2%), and inadequate collaboration with other healthcare professionals (56; 46.7%). CONCLUSION: Community pharmacists in Ibadan demonstrated good practice and positive attitudes towards PC provision. However, further work should emphasise on improving PC understanding, better collaboration among other healthcare professionals and overcoming system-related barriers.